THE INFLUENCE OF MEDIA TRACK WEST TOWARDS UPGRADING VOCABULARY STUDENTS OF SMA NEGERI 5 PADANG SIDEMPUAN - Batubara, Melvariani Syari; Hadinata Rambe, Indra; Nanda, Nanda; Try Winda4, Amisha (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this research is to improve vocabulary mastery in SMA Negeri 5 Padang Sidempuan with the use of Media Track West is expected to achieve the purpose of this research. The research approach used is Classroom Action Research. This research was conducted SMA Negeri 5 Padang Sidempuan, in August 2022. The research subjects of amounting to 31 students. Data collection methods used include: documentation, observation and tests. Data analysis techniques used to determine the increase of vocabulary mastery used test that was tested after the action compared the giving of the material before using the song method used likert scale with four choices that is good, enough and less to 12 aspect of teacher, 20 aspect of student vocabulary improvement. Based on the research results can be concluded that with the use of song method (singing) can: improve the mastery of vocabulary students SMA Negeri 5 Padang Sidempuan academic year 2021/2022. Evident from 31 students whose vocabulary is not good at cycle I activity with average score 67,9 increase at the end of cycle II become 83,87 of student of SMA Negeri 5 Padang Sidempuan academic year 2021/2022. Evidenced by the increase of the percentage of students' learning mastery from 54.84% in the cycle I activity to 90.32% at 90.32% percentage standard that is good qualification at the end of cycle II activity. Suggestions that can be given through this research are 1) song media can be used to improve vocabulary mastery; 2) media track can be used to improve student activity; 3) to the teachers especially art teachers can use the song media in the process of delivering language learning; 4) Singing can be used by teachers to train students to express themselves so that children's activities develop.